La cultura organizacional en la Gerencia Sub Regional de Ucayali-Contamana, periodo 2022 - Prada Macedo, Grecia Raquel (2024)
The objective is to describe the organizational culture in the Sub Regional Management of Ucayali-Contamana, period 2022. This type of study involves descriptive analysis and quantitative methods, with a non-experimental, transversal and simple descriptive research approach. The sample is 70 public servants chosen at random from a population of 91. A survey with a 60 question questionnaire was used to evaluate organizational culture, with ordinal scale responses. Organizational culture has a positive influence on the first dimension. Adaptive organizational culture is also beneficial. The third dimension is the cohesion of the business culture, which is also positive. Finally, the fourth dimension is the mission of a favorable organizational culture. The organizational culture of the Sub Regional Management of Ucayali-Contamana, period 2022 is greater than 50%.